(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The Ambassadors, as James himself claimed in the Preface to the New York Edition, is quite the best, ’all round’, of all my productions. It does repay an exhaustive study from many angles. James found the germ of the story in the word of advice W.H. Howells had given to Jonathan Sturges, as reported by him to the novelist. This young American was told by W.H. Howells that while he was young, he should make the most of his life. James saw in it material for a story and the idea that came to James’ mind, we are told in the note books, was the figure of an elderly man who hasn’t ’lived’, hasn’t at all, in the sense of sensations, passions, impulses, pleasures. He has never really enjoyed - he has lived only for duty and conscience, lived for effort, for surrender, abstention, sacrifice.